Genesis Of The Development Of Contractual Legal Relations Of Medical Services - Abdullaev Jamshid Djamilovich (Genius Journals, 2024)
The article analyzes issues related to the genesis of the development of medical service contractual legal relations. Also, the issues of the Tsarist period of Tsarist Russia, the prosperity of Medicine in Turkestan were analyzed on the basis of educational archival sources and First-Class sources.
Keywords: Codex Hammurapi; Soxmet; Valeriu Lucian Bologa; Roman Emperor Frederick II; medical work of 15 volumes by Menase Dosan